2018
DOI: 10.1371/journal.pone.0193028
|View full text |Cite
|
Sign up to set email alerts
|

Folic acid derived-P5779 mimetics regulate DAMP-mediated inflammation through disruption of HMGB1:TLR4:MD-2 axes

Abstract: High mobility group box 1 (HMGB1) is a damage-associated molecular pattern (DAMP) protein that mediates inflammatory responses after infection or injury. Previously, we reported a peptide inhibitor of HMGB1 (P5779) that acts by directly interrupting HMGB1/MD-2 binding. Here, fingerprint similarity search and docking studies suggest folic acid derived-drugs function as P5779 mimetopes. Molecular dynamic (MD) simulation studies demonstrate that folic acid mimics the binding of P5779 at the TLR4 and MD-2 intersec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…P5779 treatment conferred a striking survival advantage in an experimental pulmonary arterial hypertension model (47). Using a molecular dynamic simulation approach and surface plasmon resonance analysis, Sun et al (48) identified that several folic acid peptides mimic the binding interaction of P5779 at the TLR4/MD-2 interaction. Addition of these P5779 mimetic peptides inhibited HMGB1-induced TNF release in cultured human macrophages.…”
Section: Peptide P5779mentioning
confidence: 99%
See 1 more Smart Citation
“…P5779 treatment conferred a striking survival advantage in an experimental pulmonary arterial hypertension model (47). Using a molecular dynamic simulation approach and surface plasmon resonance analysis, Sun et al (48) identified that several folic acid peptides mimic the binding interaction of P5779 at the TLR4/MD-2 interaction. Addition of these P5779 mimetic peptides inhibited HMGB1-induced TNF release in cultured human macrophages.…”
Section: Peptide P5779mentioning
confidence: 99%
“…In vitro Reduced HMGB1-induced TNF release from cultured human macrophages (48) Anti-HMGB1 mAb (m2G7)…”
Section: Puhnonary Hypertension In Ratsmentioning
confidence: 99%
“…Recently, it was demonstrated that folic acid mimics the binding of P5779 at the intersection of TLR4 and MD-2. These folic acid-derived P5779 mimetics inhibit HMGB1-induced TNF release in human macrophages [189]. Recombinant human thrombomodulin (rTM) significantly decreases serum HMGB1 levels and improves systemic inflammatory response syndrome (SIRS) in patients with hematological malignancies [190].…”
Section: Small Peptides and Peptidomimeticsmentioning
confidence: 99%
“…The interaction of the TLR4 complex with HMGB1 can be blocked by the small molecule inhibitor P5779 95 . P5779 acts as an MD‐2 antagonist, blocking the binding of HMGB1 to MD‐2 as monitored by SPR and the subsequent HMGB1‐dependent release of TNF‐α in human macrophages 96 . The inhibition of TLR4 activation by P5779 was ligand‐specific as it did not inhibit LPS‐dependent TNF‐α release by human macrophages 95 …”
Section: Rage and Tlr4 Crosstalkmentioning
confidence: 99%